Criminal protection of women in international law - Ahmed Hatim Jabbar Attiya,; Hussein, Alaa Naser (International Journal of Psychosocial Rehabilitation, 2020)
THE protection of women's rights has been an important and dangerous development in recent times. This is in comparison to all the past ages, when this protection began to be surrounded through international justice, which is represented by the International Criminal Court as a permanent body, unlike the temporary courts, while previously, this protection was only through international and regional covenants that are not guaranteed by a cropping and restraining system, This protection was divided into two parts. One of them is general and includes general protection for women as a natural person who has rights that have been documented internationally and derived from the fundamental rights of the human person, and it carries the consequences of any act issued by women by generalizing international responsibility and commitment to duties under penalty of traceability, equality and        stripping                   of                         this          follow-up   between               them                   and                     men. And another section decides a special protection that was not the result of the present, but was consistent with this protection through the historical development in order for women to gain their rights, and this protection, prescribed in the Rome system, was affected by the development of human rights; To serve as an envying of international humanitarian law, by delving deeper into the crimes that targeted women greatly and due to the constant character of these crimes evolving compared to their predecessors during previous wars and even using women as a weapon against the other party in the conflict, which necessitated the implementation of this protection through its harmonization in national legislation Because of its positives, despite the obstacles that were considered to have negative repercussions on the sovereignty of states and the nature of protection as a whole.In general, the International Criminal Court is competent to consider international crimes against vulnerable groups, especially women, and this is confirmed by the statute in its preamble, and therefore, as a result of the foregoing, the statute of the International Criminal Court decided a set of legal guarantees to protect women against these crimes, although its effect in protection later To commit these crimes; That is, after committing these crimes, its protective effect also appears clear, and the most important of these guarantees is the court's jurisdiction to consider these crimes, the establishment of international responsibility for them, and their compliance with the principle of non-statute of limitations of international crimes.